Strategi Pengembangan Sumber Daya Manusia Pada Usaha Sayuran Hidroponik Di CV Hidroponikita Tani Mandiri Kota Depok Jawa Barat - Ali, Sultan Zein (Universitas Galuh, 2024)
CV Hidroponikita Tani Mandiri is one of the companies that produce vegetables through hydroponic cultivation. The cultivated vegetables include green spinach and red spinach. This research aims to provide appropriate recommendations for human resource development strategies for the company. The research method used is qualitative, supported by quantitative data. Primary data collection is obtained directly through interviews and questionnaires, while secondary data is gathered through relevant journal literature, theses, and data from the Central Statistics Bureau (BPS). The sampling technique used is purposive sampling, intentionally selecting 11 individuals as samples. The data analysis in this research is conducted using SWOT analysis. The results of this study indicate that CV Hidroponikita Tani Mandiri is positioned in quadrant 1, which is a positive position as it has the strength to overcome weaknesses and possesses opportunities to minimize threats. There are 8 strategic formulations applied for human resource development in CV Hidroponikita Tani Mandiri based on the SWOT analysis.